2018
DOI: 10.1038/s41467-018-07387-4
|View full text |Cite
|
Sign up to set email alerts
|

Integrin CD11b activation drives anti-tumor innate immunity

Abstract: Myeloid cells are recruited to damaged tissues where they can resolve infections and tumor growth or stimulate wound healing and tumor progression. Recruitment of these cells is regulated by integrins, a family of adhesion receptors that includes integrin CD11b. Here we report that, unexpectedly, integrin CD11b does not regulate myeloid cell recruitment to tumors but instead controls myeloid cell polarization and tumor growth. CD11b activation promotes pro-inflammatory macrophage polarization by stimulating ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
184
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(202 citation statements)
references
References 50 publications
14
184
1
3
Order By: Relevance
“…Next, we evaluated the sensitivity of different macrophage phenotypes to MEKi in vitro and found that both 2 and 3 days of MEKi treatment significantly augmented apoptosis of M2-like macrophages ( Figure 5D ). Reprogramming rather than depletion of macrophages has been recently suggested as a successful strategy to increase sensitivity towards immunoncology (33,34). Therefore, we also sought to assess if MEKi was able to induce reprogramming of macrophages towards anti-tumor (pro-inflammatory) phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we evaluated the sensitivity of different macrophage phenotypes to MEKi in vitro and found that both 2 and 3 days of MEKi treatment significantly augmented apoptosis of M2-like macrophages ( Figure 5D ). Reprogramming rather than depletion of macrophages has been recently suggested as a successful strategy to increase sensitivity towards immunoncology (33,34). Therefore, we also sought to assess if MEKi was able to induce reprogramming of macrophages towards anti-tumor (pro-inflammatory) phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…[33][34][35] Furthermore, a former study showed that pharmacological activation of CD11b/ CD18 could promote pro-inflammatory macrophage polarization and suppress tumor growth in animal models of murine and human cancer. 36 CR3 and CR4 were proved to enable complement-dependent cell cytotoxicity toward antibody-coated tumor cells as part of biological therapy. 37 As revealed in our sub-network, KEGG pathways were also predicted correlations with the hematopoietic cell lineage and immunodeficiency, providing a clue that ITGAM, ITGB2 and ITGAX might also be involved in AL amyloidosis progression via regulating immune response.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the therapeutic relevance of PG2 as a potential CSC-targeting pharmacological agent and putative component of an effective anticancer therapeutic strategy for patients with NSCLC. TAMs/MDMs display of an anti-cancer phenotype and association with reduced angiogenesis, reversed immune suppression, acquisition of a benign phenotype, repressed invasiveness, and invariably disease remission (Davies et al, 2013;Hagemann et al, 2009;Schmid et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To gain some mechanistic insight into the observed PG2 pharmacological activities, we examined its effect on cancer-complicit component of the inflammatory cascade the nuclear factor kappa protein, beta subunit (NF-B) (Shigdar et al, 2014), pro-angiogenic marker CD31 and pro-inflammatory macrophage marker CD11b (Schmid et al, 2018). Using tumor samples obtained from the mice, we demonstrated that treatment with 0.5 mg/kg/day cisplatin alone, 3 mg/kg/day PG2 alone, or PG2/cisplatin combination down-regulated the expression of NF-B, and CD31proteins mildly, moderately and strongly, respectively, while up-regulating CD11b protein expression level in increasing order of magnitude (Fig.…”
Section: Pg2 Suppresses Tumorigenicity and Metastasis In Syngeneic C5mentioning
confidence: 99%